Youth has a right to happiness, 1929 (1929)
1929 "Youth has a right to happiness, 1929" [EP0097], 1929 This Labour Party leaflet was distributed as part of its 1929 General Election campaign. This was the first election after the 1928 Representation of the People Act established equal franchise at 21 years of age.